2015
DOI: 10.1007/s10856-015-5517-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterisation of a decellularised bovine osteochondral biomaterial for cartilage repair

Abstract: It is proposed that an acellular natural osteochondral scaffold will provide a successful repair material for the early intervention treatment of cartilage lesions, to prevent or slow the progression of cartilage deterioration to osteoarthritis. Here, we investigated the efficacy of methods for the decellularisation of bovine osteochondral plugs. The plugs were subject to four freeze/thaw cycles followed by two cycles of washes in hypotonic solution and low concentration (0.1 % w/v) sodium dodecyl sulphate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Our decellularization protocol using chABC resulted in a 94% decrease in dsDNA/WW, in keeping with previous studies [ 34 , 35 ]. Furthermore, similar to these previous studies, the final dsDNA content reported here falls below the 50 ng/mg ECM dry weight threshold for prevention of adverse host reactions described by Crapo et al [ 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our decellularization protocol using chABC resulted in a 94% decrease in dsDNA/WW, in keeping with previous studies [ 34 , 35 ]. Furthermore, similar to these previous studies, the final dsDNA content reported here falls below the 50 ng/mg ECM dry weight threshold for prevention of adverse host reactions described by Crapo et al [ 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, preparing an osteochondral ECM scaffold by decellularization can provide a means of recreating osteochondral tissue architecture. Recently, though several studies have reported that osteochondral ECM scaffold was fabricated and applied to osteochondral defect repairing, its evaluation in cell removal effect, stratified structure retention and regeneration mechanism were still uncertain 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Histological sections from three replicate samples of cellular split-thickness porcine skin, decellularised porcine dermis and decellularised human dermis from each porcine and human donor were stained using 4′,6-diamidino-2-phenylindole dihydrochloride (DAPI) for visualisation of nuclear material. 11 A commercially available kit (DNAeasy kit, Qiagen) was used to isolate the DNA from control split-thickness porcine skin, decellularised porcine dermis and decellularised human dermis. Six replicate samples per pig/donor in each group were processed.…”
Section: Methodsmentioning
confidence: 99%